Interpretasi Narasi Ayat-Ayat Eskatologis Dalam Juz ‘Amma - Jamiatussoraya, Jamiatussoraya (STAI Darul Kamal NW Kembang Kerang, 2022)
The Qur'an tries to explain or put forward logical evidence about the existence of the last day based on justice, every action must get a reward. About eschatology is an attempt to inform the moral condition of society. Acceptance of the truth of the existence of the last day is evidence of the existence of God's justice. Belief in life after death can encourage people to do good for life after death. Writing this thesis aims to answer two problem formulations, namely how to describe the general narrative of the verses of Doomsday (eschatological) in Juz 'Amma and how to interpret the verses of Doomsday (eschatological) in Juz 'Amma. This research is a library research, using a descriptive analysis method, namely describing or giving an overview of the object under study through the data that has been collected. As a result, the general description of the Day of Judgment in juz amma is expressed with metaphorical expressions and according to some commentators such as M.Quraish Shihab and Muhammad Abduh, in interpreting the verses of the Day of Judgment, some tend to be textual and contextual.